The Comparison of Stock Price Before and After Pandemic to Identify The Health of Sector Company - Retinda Liandya Gita; Endang Chumaidiyah; Rita Zulbetti (International Journal of Innovation in Enterprise System, 2022)
At the beginning of the Covid-19 outbreak in Indonesia, almost all activities in this country weredisrupted and economic activity was no exception. Indonesia's current economic growth is down2.07% in 2020 due to the Covid-19 pandemic which has caused it to be reduced to a low and middleincome country. Based on the gross domestic product (GDP), most sectors of the Indonesian economyexperienced a decline in growth in 2020. Only 5 economic sectors showed positive growth. The sectorwith the largest positive growth was the health services sector and social activities, which amountedto 11.60%. This growth affects the stock price of health sector companies. Grounded on the IDXIndustry category (IDXHEALTH) from 2018-2022, there was an increase of 41.28%. The HealthSector which continues to grow is driven by the payment of Covid- 19 incentives. This study wasconducted to identify the Difference in Stock prices of Health Sector Companies before and afterCovid- 19 with the supposition that the Covid- 19 pandemic occurred in March 2020 by observingstock price fluctuations two years before and after the Covid- 19 Pandemic. Based on the PairedSample T-test, the stock prices of 3 companies from 6 companies have significant differences in thespecified sample period, namely DVLA, PRDA, and MERK companies where the stock prices ofDVLA and PRDA have increased. In addition, PRDA's stock price has the largest stock price amongother health sector companies, meaning that PRDA companies have good performance.